A woman with lip lesion and submandibular lymphadenopathy - Kaya, Abdurrahman; Kaya, Sibel Yıldız; Durmaz, Gamze; Mıkayılova, Nurlana (Sociedad Espanola de Enfermedades Infecciosas y Microbiologia Clinica, 2022)
[Abstract Not Available]
Keywords: Submandibular Lymphadenopathy; Lip Lesion; Woman